Resepsi Dialog Antar Agama di Media Sosial: Studi Kasus Youtube Deddy Corbuzier Dalam Tagar LoginCloseTheDoor - Trendi, Hadiana; Aulya Afifah, Tsaqifa; Azami, Hadiana Trendi; Afifah, Tsaqifa Auliya; Mumtaz, Ghina Syaikhah (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2024)
The trend of using social media for da'wah in Indonesia has sparked diverse perspectives. While some religious studies emphasize the negative aspects of social media, such as exclusivism and extremism, interreligious dialogue studies often focus on theological and ritualistic aspects. This study addresses a gap by analyzing the reception of interreligious dialogue on social media, specifically through a case study of Deddy Corbuzier's YouTube channel using the hashtag #LoginCloseTheDoor. Utilizing a qualitative approach, this research examines audience responses, both positive and negative, and the potential social impact of these dialogues. The study seeks to answer two key questions: How does Deddy Corbuzier's interreligious dialogue content under the hashtag #LoginCloseTheDoor influence social media users? What factors drive netizens to engage enthusiastically with this content? Findings indicate that the